2021
DOI: 10.1371/journal.pone.0249963
|View full text |Cite
|
Sign up to set email alerts
|

Institutional investors and cost of capital: The moderating effect of ownership structure

Abstract: Guiding institutional investors to actively participate in corporate governance is a hot issue to improve the internal governance of China’s listed companies. This study seeks to provide a comprehensive understanding of the mechanism that underlies the governance effects of the heterogeneity of institutional investors on the cost of capital, and the influence of ownership structure on the relationship between them. Using an unbalanced panel data on A-share listed companies of Shanghai and Shenzhen in China’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In this study we re-examine this issue by focussing on another analyst outcome, namely stock recommendation, rather than analyst following. Additionally, in China, Huo et al. (2021) show that institutional investors' governance roles are undermined in firms with greater ownership concentrations since they have lower influence in decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we re-examine this issue by focussing on another analyst outcome, namely stock recommendation, rather than analyst following. Additionally, in China, Huo et al. (2021) show that institutional investors' governance roles are undermined in firms with greater ownership concentrations since they have lower influence in decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the company is also linked with the financial stability and liquidity of the enterprise. Institutional investors are generally the financial institution that holds a large number of deposits of small individual, they include banks and other financial institutions [10]. At the time of any liquidity issues and solvency issues, that may arise when the company's current liabilities become more than the current assets or when the company needs additional capital in the form of debt.…”
Section: Introductionmentioning
confidence: 99%
“…The institutional investors want to earn high profits in the form of returns from their share that can be achieved when the corporate governance decides for the benefits and growth of the company. Apart from that, it was also found that the institutional investors play a dominant role in the stock market that allows them to turn this capitalist form of the system into a system wherein the financial institutions have the privilege in terms of both productions as well as in the financial investment [10]. The institutional investors present in the market ensure that the proper flow of funds in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional investors are a significant source of capital with significant financial strength and investment potential [4], and a large body of research examines whether institutional investor stockholding can increase the value of the company owned. The available literature on institutional investors' role can be divided into three groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the literature on the impact of institutional investors' holdings on firm value lacks consensus. Furthermore, despite several studies investigating the heterogeneity of institutional investors and discovering that securities investment funds, QFIIs, and social security funds differ in their enthusiasm for participating in corporate governance, value selection, or value creation roles, there is limited research on the heterogeneity of institutional investors [4,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%